Angelman syndrome resulting from UBE3A mutations in 14 patients from eight families: clinical manifestations and genetic counselling. Issue 7 (1st July 1999) - Moncla, Anne; Malzac, Perrine; Livet, Marie-Odile; Voelckel, Marie-Antoinette; Mancini, Josette; Delaroziere, Jean Christophe; Philip, Nicole; Mattei, Jean-François
Abstract : Angelman syndrome (AS) is a neurological disorder with a heterogeneous genetic aetiology. It most frequently results from a de novo interstitial deletion in the 15q11-q13 region, but in a few cases it is caused by paternal uniparental disomy (UPD) or an imprinting mutation. The remaining 20 to 30% of AS patients exhibit biparental inheritance and a normal pattern of allelic methylation in the 15q11-q13 region. In this latter group, mutations in the UBE3A gene have recently been shown to be a cause of AS. Here we describe the phenotypic expression in 14 AS cases involving eight UBE3A mutations. These comprise 11 familial cases from five families and three sporadic cases. Subtle differences from the typical phenotype of AS were found. Consistent manifestations were psychomotor delay, a happy disposition, a hyperexcitable personality, EEG abnormalities, and mental retardation with severe speech impairment. The other main manifestations of AS, ataxia, epilepsy, and microcephaly, were either milder or absent in various combinations among the patients. In addition, myoclonus of cortical origin was frequently observed with severe fits inducing myoclonic seizures. The majority of the patients were overweight. This study showed that ataxia, myoclonus, EEG abnormalities, speech impairment, characteristic behavioural phenotype, and abnormal head circumference are attributable to a deficiency in the maternally inherited UBE3A allele. Furthermore, analysis of mutation transmission showed an unexpectedly high rate of somatic mosaicism in normal carriers. These data have important consequences for genetic counselling.